GASTRONOMY AND CULINARY ARTS EDUCATION IN TURKEY: DEPARTMENT HEADS’ PERSPECTIVE - EKINCEK, Sema; OZGUR GODE, Merve; ONCEL, Sibel; YOLAL, Medet (Studia Universitatis Babeș-Bolyai Negotia, 2017)
This study investigated how gastronomy and culinary arts department heads perceived their programs and what their expectations were about the future of their field. A qualitative design was employed to collect data from the department heads. A total of nine department heads participated in the study. Findings revealed that course content was the most important concern, followed by the internship problems. Postgraduate programs were also desired for educating the necessary academics specialized and experienced in the field. Academic events and contests are also found to be important in supplementing and supporting the gastronomy and culinary arts education. JEL Classification: I22